Globalisation of Asian fashion brands. - Seet, Mei Mei. (2008)
This study focuses on the globalisation of the fashion industry. Characteristics of both international and Asian fashion brands are analysed and a positioning model is formulated along with specialised recommendations for Asian fashion brands to facilitate their branding strategies in expanding beyond regional borders.